The Role of Parents in Family Education on Surah At-Tahrim (Study of Interpretation Maudhū'ī li Sūrah Wāhidah) - Akhmad Syahbudin; Abd. Basir; Abdullah Karim; Mahyuddin Barni (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2022)
The role of parents in the process of family education is a necessity that cannot be avoided because of the critical role of the Family as the environment of origin and the first environment for humans. The existence of the Family is significant in supporting the achievement of educational goals. Various facts and realities on the ground show that the role of the Family today has not shown its maximum effort as the primary educational institution, resulting in the practice of violence in the Family, contrary to fundamental principles in the educational process. This paper intends to explore the critical role of parents in family education in every educational process based on the viewpoint of the Qur'an in surah at-tahrim (study of the interpretation of maudhu'i li sura wahidah). This exploration is intended to obtain the fundamental essence of the role of parents in the family education process so that it can provide a new perspective in perceiving the Family as an essential part of the humanization process.